Obesity, Overweight Rates, and Related Factors Among Adults in the Rustic Realm of Western India - Patel, Monika; Kagathara, Jimmy; Gupta, Eshwar Kumar; Kagathara, Nancy; Mehta, Jitesh; Parmar, Dipesh (UI Scholars Hub, 2023)
Background: Obesity and overweight pose significant challenges in developing countries, underscoring the need for evidence-based prevention strategies. This study focuses on assessing the prevalence and associated factors of overweight and obesity in the rural areas of Jamnagar district, Gujarat, India. Methods: Data collection encompassed six tehsils within Jamnagar district, with primary health center selection via simple random sampling. Individual selection employed the consecutive sampling approach. Statistical analysis was conducted using SPSS software. Regression analysis was employed to identify the independent factors linked to overweight and obesity. Results: The analysis included 408 participants, revealing a higher obesity prevalence among men (20.8% vs 13.5%). Strong evidence suggests that married and physically inactive individuals have 2.8 times higher odds of being overweight or obese. After thorough adjustments, homemakers and physically inactive individuals had 5.9-fold higher odds. Conclusions: The study findings illuminate a pronounced prevalence of overweight and obesity among adults in the study area, signifying an emerging issue that necessitates prompt attention.